The Effects of Service Quality and Positive Recommendation on Trust Building in Mobile Banking Adoption Among the Customers of Private Banks in Myanmar - Phyo Min Tun (JASF: Journal of Accounting and Strategic Finance, 2021)
This study attempts to follow the research direction and fill the research gaps of previous studies, most notably the mobile financial service landscape, specifically mobile banking (MB) services of private banks in Myanmar. The proposed research model in this study emphasizes service quality, positive recommendations, and different perspectives of trust namely: trust in banks and trust in MB, and evaluated their extent of influence on customers of private banks to adopt MB. The data was collected from 310 customers of private banks in Myanmar. Structural equation modeling (SEM) and confirmatory factor analysis (CFA) were employed to analyze the data and investigate the hypotheses. The analysis results indicate that customer intention to adopt MB is significantly influenced by trust in MB however trust in the bank was found to be statistically insignificant. The positive recommendation plays a critical role in the improvements of trust in the bank and MB according to the research results. Although service quality is a key factor in obtaining positive recommendations and acquiring trust in the bank, it is an insignificant factor in building trust in MB. Further, trust in the bank has a significant effect on trust in MB. These findings are highly beneficial for future research studies in a similar context and for bank managers to develop appropriate strategies regarding MB services in the private banking sector in Myanmar.